The Akroma File. - Asong, Linus T. (Linus Tongwo), 1947-2012 (Langaa RPCIG, 2009)
Faced with debts at home and threatened by poverty, Akroma a brilliant and well-educated Ghanaian, using unorthodox means, successfully gets into Cameroon. He is bent on making a fortune. Drawing on his tremendous presence of mind and, capitalising on the early discovery that in Cameroon there is no conscience that money cannot buy, this illegal alien, travelling under three criminal identities, builds up a great amount of wealth. But he cannot buy the entire police force. One police man, Inspector Kum Dangobert, will get even with him, even if it means death. The rest of this very readable no.